2019
DOI: 10.26452/ijrps.v10i2.260
|View full text |Cite
|
Sign up to set email alerts
|

Antidermatophytic, the anticancer and antioxidant activity of Cassia alata ethanolic extract and its phytochemical analysis

Abstract: Cassia alata is used traditionally to cure various diseases like ulcers, stomach pain and fever. The potential of antidermatophytic, free radical scavenging and cytotoxic activity of ethanol leaves extracts of C. alata was studied. The preliminary phytochemical screening assay elucidates that presence of carbohydrates, tannin, phenol, saponin, flavonoid, steroid, terpenoids, glycosides, and alkaloids. Further phytochemical extraction was done by GC-MS, HPLC and FTIR. GC-MS analysis confirms that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…A low susceptibility level was observed for T. mentagrophyte, T. tonsurans, T. rubrum, M. audouinii and M. gypseum. This agrees with Sujatha and Asokan (2018), who reported the antifungal activity of hexane extract of Cassia alata leaves against strains of M. canis, T. mentagrophytes, T. rubrum, E. floccosum, and M. audouinii but with varying concentrations.…”
Section: Resultssupporting
confidence: 92%
“…A low susceptibility level was observed for T. mentagrophyte, T. tonsurans, T. rubrum, M. audouinii and M. gypseum. This agrees with Sujatha and Asokan (2018), who reported the antifungal activity of hexane extract of Cassia alata leaves against strains of M. canis, T. mentagrophytes, T. rubrum, E. floccosum, and M. audouinii but with varying concentrations.…”
Section: Resultssupporting
confidence: 92%
“…Natural antioxidants from plants and microorganism have been known to act as potent preventive therapy for treating reactive oxygen species related to various ailments like diabetes mellitus, cardiovascular and neurodegenerative diseases and aging (Sujatha & Asokan, 2017). The antiradical activity of the isolated endophytic fungi and host organs extracts were evaluated for their capacity to scavenge the DPPH radical.…”
Section: Free Radical Scavenging Ac Vitymentioning
confidence: 99%
“…Hassan et al [ 8 ] stated that the active compound of C. alata leaf extract inhibits fungal cell walls due to the formation of pores in cells and leakage of cytoplasmic constituents. A study by Edegbo et al [ 9 ] showed that n-hexane extract has higher antifungal activity than aqueous, chloroform, methanol, and ethanol extracts and is most active against Epidermophyton floccosum and M. canis , while Sujatha et al [ 10 ] reported that the n-hexane extract of C. alata leaves has antifungal activity against M. canis, M. audouinii, T. mentagrophytes, T. rubrum , and E. floccosum at various concentrations. The chloroform extract of C. alata leaves was also reported to have antifungal activity against fungal isolates, including E. floccosum, M. gypseum , and T. mentagrophyte [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%